IMPLEMENTATION OF HYBRID VLAN NETWORK CONFIGURATION - Michael Jordan; Joseph Dedy Irawan; Yohanes Yudha Saputra Bangko; Maqila Sulaiman Abu Zakaria (Computer Science Department, Malang National Institute of Technology, 2024)
The need for internet access has become a necessity provided by all agencies, where in the research conducted on campus 2 of the National Institute of Technology Malang, where the VLANs distributed are approximately 25, so that in distributing internet access requires good network management, where by implementing Hybrid VLAN the IP distribution process is easier and increases the efficiency of network management, by using Hybrid VLAN, the trunking process and IP access are carried out on the router side, From the results of the Implementation of Hybrid VLAN Network Configuration on the ITN Malang Infrastructure, it can be concluded as follows: The implementation of Hybrid VLAN has succeeded in increasing network efficiency by separating network traffic based on function and department, thereby reducing traffic density and improving overall performance, By separating the network into several VLANs, the level of isolation between various network segments has increased, which has an impact on increasing security and reducing the risk of unauthorized access, by implementing a Hybrid VLAN Network, network administrators can manage bandwidth according to the needs of the VLAN segment easily and quickly